Factors Related to Covid-19 Prevention Behaviour on Market Traders in Pontianak - Sukemi, Maria Yolan; Trisnawati, Elly; Selviana, Selviana (Sean Institute, 2022)
Informal sector workers are one of the workgroups that are vulnerable to contracting Covid-19, because they interact more directly with many people, so they can increase the risk of spreading a disease. The report by the Satuan Tugas Penanganan COVID-19 as of May 8 2022 shows that the cumulative number of people who are reprimanded related to 3M based on the location of the crowd is occupied by